2021
DOI: 10.1016/s2468-2667(20)30288-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID-19 pandemic on primary care-recorded mental illness and self-harm episodes in the UK: a population-based cohort study

Abstract: Summary Background The COVID-19 pandemic has adversely affected population mental health. We aimed to assess temporal trends in primary care-recorded common mental illness, episodes of self-harm, psychotropic medication prescribing, and general practitioner (GP) referrals to mental health services during the COVID-19 emergency in the UK. Methods We did a population-based cohort study using primary care electronic health records from general practices regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
237
4
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(289 citation statements)
references
References 29 publications
29
237
4
4
Order By: Relevance
“…The incidence of self-harm recorded in primary care was substantially lower than expected for 10-17 year olds in April 2020 but returned to pre-pandemic levels by September 2020 19. Similar patterns were detected for all mental health referrals in England,20 with reductions in urgent psychiatric presentations reported across Europe,21 suggesting possible unmet need.…”
mentioning
confidence: 60%
“…The incidence of self-harm recorded in primary care was substantially lower than expected for 10-17 year olds in April 2020 but returned to pre-pandemic levels by September 2020 19. Similar patterns were detected for all mental health referrals in England,20 with reductions in urgent psychiatric presentations reported across Europe,21 suggesting possible unmet need.…”
mentioning
confidence: 60%
“…To our knowledge, only one population-based study reported a lower incidence of self-harm in the United Kingdom in April 2020 compared with the previous years, especially in women and people younger than 45 years. 4 In France, the first national lockdown was from March, 16 to May, 11 2020 (home confinement, limited social contacts, closure of schools and of all unnecessary business activities). We used the French national hospital discharge database (Programme de Médicalisation des Systèmes d'Information, PMSI) to identify SA-related hospitalizations (ICD-10 codes X60 to X84) in Medicine/Surgery services of publicand private-sector hospitals.…”
Section: Hospitalizations For Suicide Attempt During the First Covid-19 Lockdown In Francementioning
confidence: 99%
“…Our results are consistent with the observed decrease of suicidal behaviours in many countries during the strict lockdown. 4,5 This decrease may be explained by several factors: the so-called "pulling-together effect" observed in times of national tragedies, the work adaptation (reduced working hours and work-from-home policies), the subsidies to limit financial distress, the reduced access to illegal drugs. However, the absolute number of violent or severe SA (and related deaths during hospitalization) remained relatively stable.…”
Section: Hospitalizations For Suicide Attempt During the First Covid-19 Lockdown In Francementioning
confidence: 99%
“…Rates of self-harm and common mental health conditions were lower than expected in primary care during the early stages of the pandemic, but concern remains about a possible rebound effect causing higher rates of mental health problems, self-harm, and suicide in the coming months and years 17…”
mentioning
confidence: 90%